Development of Physics Mobile Learning Integrated with Games on Temperature and Heat Materials - Ahadillailah, Aulia; Suherman, Andri; Saefullah, Asep (Jurnal Pendidikan MIPA, 2022)
This study aims to develop learning media in the form of learning videos of Phymol (Physics Mobile Learning) Integrated Games on the material of Temperature and Heat. The research method used is the R&D (Research and Development) research method with the ADDIE development model, including the stages of Analysis (analysis), Design (design), Development (development), Implementation (implementation) and Evaluation (evaluation). In this study, the product was validated using an expert validation instrument which was distributed to two lecturers and three teachers and a limited trial was conducted using student response questionnaires. The results of product validation show an average percentage of 92% with a very feasible category. The limited trial conducted by the researcher involved 30 students of SMA Negeri 5 Cilegon. Student responses showed an average percentage of 86% with a very good category. Based on the results of expert validation and student response questionnaires, physics learning media in the form of Phymol learning videos (Physics Mobile Learning) integrated Games on Temperature and Heat material is very feasible and can be used as a physics learning medium. Keywords: physics learning, games, temperature and heat . DOI: http://dx.doi.org/10.23960/jpmipa/v23i1.pp111-122